Aborsi dalam Perspektif Gereja Katolik: Telaah Moral dan Teologis - Koli, Arnoldus Nofrianus; Terang, Erfianus Moat; Bili, Teofilus Xaverius; Locang, Georgius (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Abortion is a complex and controversial moral and theological issue, especially in the context of the teachings of the Catholic Church. This study aims to examine the Catholic Church's views on abortion with a moral and theological approach, based on Sacred Scripture, Church Tradition, and Magisterium documents such as Evangelium Vitae and Gaudium et Spes. In the light of Catholic teaching, abortion is seen as an intrinsically wrong act because it takes innocent human life from the moment of conception. The study also examines the anthropological and ethical foundations underlying the Church's respect for the dignity and right to life of every human being. In addition, the pastoral dimension of the Church in dealing with the reality of abortion is discussed, including assistance to women who experience moral dilemmas. The results show that the Catholic Church is consistent in defending life from conception to natural death, while inviting people to develop a culture of life based on love, forgiveness and repentance. Thus, the Church's view on abortion is not merely a prohibition, but a call to respect life as a divine gift.